Pemikiran Fikih Perempuan dalam Kitab Parukunan Banjar - Yamani, Antung; Ariyadi, Ariyadi; Muhammad Wahdini (LP2M Universitas Islam Ahmad Dahlan, 2023)
This paper discusses the thoughts of Banjar women scholars as outlined in the great Parkununan book. The book which was originally given the name